2009
DOI: 10.3945/ajcn.2009.26736v
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the soy–breast cancer relation

Abstract: There has been considerable investigation of the potential for soy foods to reduce risk of breast cancer. Initial enthusiasm for this research was partially based on the historically low incidence rates of breast cancer and high soy food intake in Japan. There are several putative soybean chemopreventive agents, but most cancer research has focused on isoflavones. Isoflavones possess both hormonal and nonhormonal properties relevant to carcinogenesis. Recent epidemiologic analyses indicate that among Asians hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 161 publications
(104 reference statements)
2
57
1
2
Order By: Relevance
“…However, it is noteworthy that Japanese incidence rates of breast cancer have increased markedly during the last decades, along with Westernization of the diet and culture, while simultaneously breast cancer has become the number one type of cancer among Japanese women (http://www.mc.pref.osaka.jp/ocr/). The results of the epidemiological studies published are confusing, and evidence suggests that plasma or serum concentrations of IFs may be a more sensitive predictor of the possible protective effects of soy foods against breast cancer than the assessment of dietary IFs intake (Messina & Wu, 2009), mainly due to the marked differences in IF metabolism that exist among individuals, as well as differences in sources of IFs, differences in biological response to IFs among ethnic groups, interactions with background diet, among others. Consequently, plasma IF levels are more reliable biomarkers compared with dietary IFs intake for evaluating the potential of soy to reduce breast cancer risk.…”
Section: Breast Cancermentioning
confidence: 95%
“…However, it is noteworthy that Japanese incidence rates of breast cancer have increased markedly during the last decades, along with Westernization of the diet and culture, while simultaneously breast cancer has become the number one type of cancer among Japanese women (http://www.mc.pref.osaka.jp/ocr/). The results of the epidemiological studies published are confusing, and evidence suggests that plasma or serum concentrations of IFs may be a more sensitive predictor of the possible protective effects of soy foods against breast cancer than the assessment of dietary IFs intake (Messina & Wu, 2009), mainly due to the marked differences in IF metabolism that exist among individuals, as well as differences in sources of IFs, differences in biological response to IFs among ethnic groups, interactions with background diet, among others. Consequently, plasma IF levels are more reliable biomarkers compared with dietary IFs intake for evaluating the potential of soy to reduce breast cancer risk.…”
Section: Breast Cancermentioning
confidence: 95%
“…Comparison of biopsies taken before and after exposure to soy products did not show increased cell proliferation in any of the four different trials involving breast cancer patients, healthy subjects, and women undergoing breast biopsy or definitive surgery for breast cancer. Daily isoflavone intake in these trials ranged from 36 to more than 100 mg, with study periods ranging from 2 weeks to one year (Messina et al, 2009). Another study examining more than one breast cancer biomarker found no statistically significant differences in cell proliferation (Ki67 index), histology (hyperplasia with or without atypia), or ER expression in 6 and 12 months of soy intake (Messina et al, 2006).…”
Section: Aspects Of Isoflavone Intake In Humansmentioning
confidence: 99%
“…Thus, a better comprehension of the current existing animal models and the development of new ones would contribute to the interpretation and translation of isoflavone effects in humans. Given the conflicting data and limited in vitro and in vivo models, the controversy about the effects of isoflavones either from soy foods or supplements would be unlikely solved by additional animal research (Messina et al, 2009). Then, epidemiologic data should be another alternative to study and conclude about isoflavone intake and breast cancer.…”
Section: Dose-dependent Effectsmentioning
confidence: 99%
“…Isoflavones and saponins have been implicated in potential health benefits related to age-related and hormone dependent diseases, including breast and ovarian cancer, menopausal symptoms, mammary, cardiovascular disease, and osteoporosis (Anderson et al, 1995;Yoshiki et al, 1998;Setchell and Cassidy, 1999;Kulling et al, 2002;Messina and Wu, 2009;Keatinge et al, 2011). There is some evidence, mostly in animal studies, that soya saponins can lessen the rate of lipid peroxidation in blood vessels, as well as absorption of cholesterol from GI tract, and increase excretion of fecal bile acids.…”
Section: Roles Of Seed Chemical Compoundsmentioning
confidence: 99%